Cermet cosmetic item
The thermet material with a ceramic phase and precious metal binder addresses the issue of allergic metal binders and moisture control in nitride-based thermets, achieving high scratch resistance and toughness for decorative items like watch cases and jewelry.
Patent Information
- Application Number
- JP2023512442
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-09
- Filing Date
- 2021-07-07
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2041-07-07
Smart Images

Figure 0007624507000004 
Figure 0007624507000005 
Figure 0007624507000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a decorative item, in particular an external component of a timepiece, made of a cermet type material, which comprises a ceramic phase comprising a nitride and a metallic phase comprising a precious metal. [Background technology]
[0002] Nitride-based colored cermets contain allergy-inducing metallic binders such as nickel or cobalt. For the production of parts that may come into contact with the skin, such as watch cases or jewels, it is essential to develop compositions that do not use binders with these elements.
[0003] Furthermore, cermets used for certain applications such as watch cases must have very high scratch resistance, i.e., hardness of more than 1,000 HV. This requires reducing the amount of metal binder while controlling the wettability between the metal binder and the ceramic phase. Poor wettability reduces the density of the final product and therefore the hardness. In particular, it is difficult to produce yellow titanium nitride (TiN)-based colored cermets that are nickel- and cobalt-free and have good final properties by powder metallurgy and conventional liquid phase sintering. This is mainly due to the very high melting point of titanium nitride, 2,930°C, which results in poor wettability with the metal binder during liquid phase sintering. As a result, the cermets are highly porous at the end of sintering and have low hardness.
[0004] In addition to hardness, the proportions of the different phases must also be adjusted so that high toughness and the desired color are obtained in the final product. Summary of the Invention
[0005] The aim of the present invention is to propose a cermet having an optimal composition that meets the following criteria and thus overcomes the aforementioned drawbacks: -Does not contain allergenic elements such as nickel or cobalt, - Densification is possible by liquid phase sintering under low pressure (conventional sintering), For applications where very high scratch resistance is required, preferably 2.8 MPa.m 1 / 2 More than K iC While having sufficient toughness to have a minimum hardness of 500 HV30, preferably a minimum hardness of 550 HV30, and more preferably a minimum hardness of 1,000 HV30; -It has a white to yellow color and a high metallic luster (65 <L*≦80)。
[0006] The invention therefore proposes a decorative item made of a cermet material, the cermet material comprising 70 to 97% by weight of a ceramic phase and 3 to 30% by weight of a metal binder phase, the metal binder comprising at least one element or an alloy thereof selected from the list consisting of ruthenium, rhodium, palladium, osmium, iridium, platinum, gold and silver, the ceramic phase comprising a nitride phase and optionally an oxide phase and / or an oxynitride phase, the nitride phase being present in a proportion of 70 to 97% by weight and the oxide phase and / or the oxynitride phase being present in a proportion of 0 to 15% by weight, relative to the total weight of the cermet material.
[0007] Specifically, for the production of titanium nitride (TiN)-based yellow cermets by powder metallurgy and conventional liquid phase sintering, it is proposed to promote densification and increase hardness by adding oxides and / or oxynitrides.
[0008] The cermet materials developed in this way have, after polishing, a metallic luster that exceeds that of cermets using nickel or cobalt as metal binders and is comparable to that of stainless steels (L*=75-80). These valuable cermets have a hardness that can reach 1,250 HV30 and are tough enough to manufacture external components. Moreover, these cermets can be formed by conventional powder metallurgy such as compression or injection to obtain 3D parts with a "near net shape" close to the finished product.
[0009] Other characteristics and advantages of the invention will become apparent from the following description of preferred embodiments given as non-limiting examples with reference to the attached drawings, in which: [Brief description of the drawings]
[0010] [Figure 1] 1 shows a timepiece with a body made of a cermet-type material according to the invention. [Diagram 2] 1 shows an optical microscope image of a cermet type material according to the invention having a composition by weight of 92% TiN and 8% Pd. [Diagram 3] 1 shows an optical microscope image of a cermet type material according to the present invention having a composition by weight of 84.6% TiN, 9.4% zirconium oxide (ZrO2), and 6% Pd. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention relates to a decorative item made of a cermet type material. The cermet type material comprises (consists of) 70 to 97% by weight of a ceramic phase and 3 to 30% by weight of a metal binder phase. Preferably, the cermet comprises (consists of) 75 to 97% by weight of a ceramic phase and 3 to 25% by weight of a metal binder phase. More preferably, the cermet comprises (consists of) 78 to 96% by weight of a ceramic phase and 4 to 22% by weight of a metal binder phase. The metal binder is selected from the list of elements comprising ruthenium, rhodium, palladium, osmium, iridium, platinum, gold and silver. The metal binder may also concern a combination of several of these elements or a combination of alloys of one of these elements, for example Au-3N, Au-5N. The ceramic phase comprises a nitride phase and optionally an oxide phase and / or an oxynitride phase. In other words, the ceramic phase consists of a nitride phase and optionally an oxide phase and / or an oxynitride phase. The purpose of the oxide and / or oxynitride phases is to increase the mechanical properties. When the oxide and / or oxynitride phases are present, they are less than the nitride phases. More specifically, the nitride phases are present in a proportion of 70 to 97 wt. % and the oxide and oxynitride phases are present in a proportion of 0 to 15 wt. % based on the total weight of the cermet. The nitrides are selected from a non-exclusive list including Al, Ti, Si, Mn, Zr, Hf, Ta, Nb, V, Cr, Mo, W, B nitrides and combinations of nitrides of these elements. The oxides and oxynitrides are selected from a non-exclusive list including Al, Ti, Si, Mn, Zr, Hf, Ta, Nb, V, Cr, Mo, W, B oxides and oxynitrides and combinations of oxides and oxynitrides of these elements, respectively.
[0012] The decorative item may be a constituent element of a watch, a piece of jewellery, a bracelet, etc. In the field of watch manufacturing, the decorative item may be an external part such as a case, a back, a bezel, a crown, a link of a bracelet, a dial, hands, indexes of a dial, etc. By way of example, a case 1 made of a cermet-type material according to the invention is shown in FIG.
[0013] Cermet items are manufactured by sintering starting from a mixture of ceramic and metal powders. The manufacturing method includes the following steps: a) producing a mixture of different powders, possibly in a humid environment. The median diameter (d50) of the starting powders is preferably less than 10 μm, more preferably between 2 and 5 μm. The mixture may possibly be produced in a mill, whereby after milling the d50 of the particles of the powder is reduced to a size of about micron or even submicron. The mixture comprises 70 to 97% by weight, preferably 75 to 97% by weight, more preferably 78 to 96% by weight of ceramic powder and 3 to 30% by weight, preferably 3 to 25% by weight, more preferably 4 to 22% by weight of metal powder. The ceramic powder comprises nitrides and optionally oxides and / or oxynitrides. More specifically, the nitrides are present in a proportion of 70 to 97% by weight, preferably 75 to 97% by weight, more preferably 78 to 96% by weight, and the oxides and / or oxynitrides are present in a proportion of 0 to 15% by weight, relative to the total weight of the powder. The nitrides are selected from a non-exclusive list including Al, Ti, Si, Mn, Zr, Hf, Ta, Nb, V, Cr, Mo, W, B nitrides and combinations of nitrides of these elements. Advantageously, the nitrides are selected from Ti, Ta, Nb, Zr nitrides and combinations of nitrides of these elements. The oxides and oxynitrides are selected from a non-exclusive list including Al, Ti, Si, Mn, Zr, Hf, Ta, Nb, V, Cr, Mo, W, B oxides and oxynitrides, respectively, and combinations of oxides and oxynitrides of these elements. Advantageously, the oxides and oxynitrides are selected from Zr or Nb oxides and oxynitrides. The metal powder is selected from the list of metallic elements including ruthenium, rhodium, palladium, osmium, iridium, platinum, gold, silver, combinations of several of these elements and alloys of one of these elements. Thus, preferably, gold is alloyed with at least one element selected from Cu, Ag, Pd, C, N. Advantageously, the metal powder comprises mainly palladium, platinum, silver, or gold alloyed with copper and / or silver. The metal powder may consist entirely of platinum, palladium, silver, or gold alloyed with copper and / or silver, apart from impurities. By way of example, the powder mixture may comprise one of the following weight distributions: - 78 to 96 wt. % TiN and 5 to 20 wt. % Pd or Pt; - 80 to 90 wt. % TiN and 10 to 20 wt. % Ag, - 75 to 85 wt. % TiN and 15 to 25 wt. % Au alloy; - 80 to 90 wt. % niobium nitride (NbN) and 10 to 20 wt. % Au alloy; - 85 to 95 wt. % NbN or tantalum nitride (TaN) and 5 to 15 wt. % Pd or Pt; -80 to 90 wt.% TiN, 5 to 15 wt.% ZrO2, and 3 to 10 wt.% Pd or Au alloy; - 75 to 85 wt% TiN, 5 to 15 wt% zirconium nitride (ZrN), and 5 to 15 wt% Au alloy; -70 to 80 wt% NbN, 5 to 20 wt% niobium pentoxide (Nb2O5), and 5 to 15 wt% Pt. b) Optionally, a second mixture can be prepared comprising the above mixture and an organic binder system (paraffin, polyethylene, etc.). c) Forcing the mixture into the shape of the desired item, for example by injection (ceramic injection molding) or compression, to form a blank. d) sintering the blank under an inert atmosphere or under nitrogen or under vacuum at a temperature between 1,100 and 2,100° C., preferably between 1,400 and 1,750° C., for a period between 30 minutes and 20 hours, preferably between 30 minutes and 2 hours. If the mixture contains an organic binder system, this step may be preceded by a debinding step at a temperature in the range of 200 to 800° C.
[0014] The blank thus obtained is cooled and polished, and may be machined prior to polishing to obtain the desired item.
[0015] The resulting item from this manufacturing method has ceramic and metallic phases with weight percentages close to those of the starting powders, although minor variations in composition and proportions may occur between the raw powders and the material resulting from sintering, e.g. due to contamination or alteration during sintering. Oxynitrides may also be formed in situ, e.g. if the starting powder contains both nitrides and oxides of the same element. The metallic and ceramic phases are uniformly distributed in the cermet material.
[0016] The items have a CIELAB color space (according to the International Commission on Illumination (CIE) Standard No. 15, lSO 7724 / 1, German Industrial Standard (DIN) 5033 Teil 7, ASTM E-1164) with a lightness L* component, which indicates the light reflectance of the material, of at least 60, preferably at least 65, more preferably at least 75. The color variations range from white, which corresponds to a steel color, to a slightly yellowish color, to a pronounced yellow. More specifically, for white items, the a* component is between -3 and +3, and the b* component is between -3 and +3. For colors between white and yellow, the a* component is between 0 and +3, and the b* component is between 0 and +10. For yellow, the a* component is between 0 and +5, and the b* component is between +20 and +30.
[0017] The ceramic material has a Vickers hardness of 500 to 1,300, preferably 550 to 1,250, depending on the type and proportion of constituents, measured under a load of 30 kg (HV30). Advantageously, the ceramic material has a hardness of more than 1,000 Vickers for external parts where very high scratch resistance is required. The ceramic material has a minimum hardness of 2 MPa.m 1 / 2 , preferably a minimum of 2.8 MPa.m 1 / 2 The toughness of iC Toughness is determined based on measuring the length of the crack at the four diagonal ends of the hardness indentation according to the following formula:
[0018]
number
[0019] where P is the applied load (N), a is the half diagonal (m), and l is the measured crack length (m).
[0020] Table 1 below contains various examples of cermets according to the invention. Values in italics and bold indicate hardness above 1,000 Vickers, 2.8 MPa.m 1 / 2 Meets the criteria of L* index greater than 75 or b* index greater than 25 for a deep yellow color.
[0021] Thirteen mixtures of powders of different compositions were prepared in a mill in the presence of a solvent. The mixtures were produced without the addition of organic binders. After drying, the mixtures were formed by uniaxial pressing and sintered in vacuum or sintered under a dynamic partial pressure of 60 mbar of argon or nitrogen at a temperature depending on the powder composition. After sintering, the samples were polished flat for accurate measurement of mechanical properties and color index.
[0022] HV30 hardness measurements were performed on the surface of the samples and the toughness was determined based on the aforementioned hardness measurements.
[0023] The Lab colorimetric values of the polished samples were measured using a KONICA MINOLTA CM-5 spectrophotometer under the conditions of SCI (specular reflection included) and SCE (specular reflection excluded) measurement, tilted at 8°, and with a MAV measurement zone of 8 mm in diameter.
[0024] From these tests it is clear that hardnesses in excess of 1,000 Vickers are obtained with the following compositions: TiN 84.6%, ZrO 29.4%, Pd 6% (Test No. 3), NbN 89.5%, Pd 10.5% (Test No. 4), TaN 89.5%, Pd 10.5% (Test No. 5), TiN 85%, Pt 15% (Test No. 6), NbN 75%, Nb2O5 15%, Pt 10% (Test No. 8), TiN 84.6%, ZrO 29.4%, Au3N 6% (Test No. 9), NbN 86%, Au 10.5%, Cu 3.5% (Test No. 12). These same compositions have a hardness of 3.3 MPa.m. 1 / 2 It has a toughness that exceeds
[0025] Specifically, comparing test no. 2 (TiN 92%, Pd 8%) with test no. 3 (TiN 84.6%, ZrO2 9.4%, Pd 6%), it can be seen that the Vickers hardness increases obviously from 590 to 1,050 when oxides are added in the case of ZrO2. The oxides allow to improve the densification, and they act as reinforcement agents to enhance the mechanical properties. In Fig. 3, a reduction in porosity (black dots) is observed when oxides are added to sample no. 3 compared to sample no. 2 in Fig. 2. Thus, the hardness is almost doubled without a significant effect on the toughness. Similarly, comparing test no. 7 with test no. 8, an increase in hardness and toughness is observed by adding Nb2O5.
[0026] Furthermore, the combination of NbN with gold alloy (test no. 12) gave hardness values of over 1,000 Vickers and 4.5 MPa.m 1 / 2 This allows for a combination of toughness exceeding 100% and a lightness L* value approaching 80, i.e. the same lightness as polished stainless steel.
[0027] When platinum in sample no. 6 is used as the binder instead of palladium in sample no. 1, this difference in the inclusion of 85% TiN shows an increase in hardness, reaching a maximum value of 1,192 Vickers hardness.
[0028] [Table 1] TIFF0007624507000003.tif100170*Au-3N:Au75%, Ag12.5%, Cu12.5%, added Table 1
Claims
1. A decorative item made of a cermet material, the cermet material comprising 70 to 97% by weight of a ceramic phase and 3 to 25% by weight of a metal binder phase, the metal binder comprising at least one element or alloy thereof selected from the list consisting of ruthenium, rhodium, palladium, osmium, iridium, platinum, gold and silver, the ceramic phase comprising a nitride phase and an oxide phase and / or an oxynitride phase, the nitride phase being present in a proportion of 70 to 97% by weight and the oxide phase and / or oxynitride phase being present in a proportion of 0 to 15% by weight, relative to the total weight of the cermet material, The oxides and oxynitrides are selected from Al, Si, Ti, Ta, Nb, and Zr oxides and oxynitrides; The decorative item, wherein the ceramic phase consists of a Nb nitride phase and a Nb oxide phase.
2. 2. The item according to claim 1, characterized in that the metal binder phase is present in a proportion of 4 to 22% by weight, the ceramic phase is present in a proportion of 78 to 96% by weight, the nitride phase is present in a proportion of 78 to 96% by weight, and the oxide and / or oxynitride phase is present in a proportion of 0 to 15% by weight, based on the total weight of the cermet material.
3. 2. The item of claim 1, wherein the metallic binder phase comprises, apart from impurities, a palladium, platinum, silver or gold alloy.
4. 10. The item of claim 1, wherein the metallic binder phase comprises a gold alloy, the gold alloy comprising one or more elements selected from copper, silver, palladium, and nitrogen.
5. 2. The item according to claim 1, characterized in that it has a Vickers hardness HV30 of 500 to 1,300.
6. 2. The item of claim 1, when the ceramic phase comprises Ta or Nb nitride and the metallic binder phase comprises Pd, when the ceramic phase comprises Nb nitrides, Nb oxides and the metal binder phase comprises Pt; when the ceramic phase comprises Nb nitrides and the metallic binder phase comprises Au alloys, 1. An item characterized by having a Vickers hardness HV30 of greater than 1,000.
7. 2. The item of claim 1, having a strength of 2.8 MPa.m 1/2 More than tough K iC An item comprising:
8. 2. The item of claim 1, characterized in that in the CIELAB color space, the item has a minimum L* component of 60.
9. 2. The item of claim 1, which is yellow in color and in the CIELAB color space, the a* component is between 0 and +5 and the b* component is between +20 and +30.
10. 2. The item of claim 1, characterized in that it is white and that in the CIELAB color space, the a* component is between -3 and +3 and the b* component is between -3 and +3.
11. 2. The item of claim 1, having a color between white and yellow, wherein in the CIELAB color space, the a* component is between 0 and +3 and the b* component is between 0 and +10.
12. 2. The item according to claim 1, characterized in that it relates to a component part of an external timepiece selected from the list comprising: a case, a back cover, a bezel, a crown, a bracelet link, a dial, hands and dial indexes.
13. A method for manufacturing a decorative item, comprising the steps of: a) producing a mixture of ceramic powder and metal binder powder, the ceramic powder comprising nitrides, oxides and / or oxynitrides, the metal binder powder comprising at least one element selected from the list consisting of ruthenium, rhodium, palladium, osmium, iridium, platinum, gold, silver or alloys thereof; b) forming a blank into which said mixture is shaped into said item; c) sintering the blank at a temperature between 1,100 and 2,100° C. for a period between 30 minutes and 20 hours; A method comprising the successive steps of: The method, wherein the ceramic powder is present in an amount of from 70 to 97% by weight and the metal binder powder is present in an amount of from 3 to 25% by weight; The oxides and oxynitrides are selected from Al, Si, Ti, Ta, Nb, and Zr oxides and oxynitrides; 4. The method of claim 3, wherein the ceramic phase of the ceramic powder consists of a Nb nitride phase and a Nb oxide phase.
14. 14. The method of claim 13, wherein the mixture of step a) comprises: - 80 to 90 wt. % NbN and 10 to 20 wt. % Au alloy; - 85 to 95 wt. % NbN and 5 to 15 wt. % Pd or Pt; - 70 to 80 wt.% NbN and 5 to 20 wt.% Nb 2 O 5 and 5 to 15 wt. % Pt; The method of claim 1, further comprising the steps of:
15. 14. The method according to claim 13, characterized in that step b) is carried out by compression or injection.
Citation Information
Patent Citations
JP1973034709A
JP1973038211A
JP1973079110A
JP1973083013A
Sintered noble metallic alloy with wear resistance
JP1982026136A